Prediction of the particle’s impact velocity due to the bubble–particle interaction causing synergic wear (2023)
Cavitation damage and hard particle erosion are some of the main sources of wear in most hydraulic machines, such as pumps or hydroturbines. However, the synergic effect of these two phenomena leads to a wear phenomenon that is often more severe than the sum of the individual effects of cavitation and hard particle erosion and that has been scarcely studied. Therefore, in this work, simplified computational fluid dynamics (CFD) simulations using 2D and 3D approaches were performed to investigate the behaviour of a particle interacting with a cavitation bubble near a solid wall under several conditions of pressure, position, bubble maximum size, and mass of the particle. All the involved variables were combined into three nondimensional variables: the dependent variable includes the impact velocity of the particle normal to the surface, while the other two variables include the particle position relative to the eroded wall and the particle mass. Through this approach, several correlations were identified, and a dimensionless function of two variables and six fitting factors was proposed to comply with those correlations. Then, this function was returned to its dimensional form to obtain an expression to predict the impact velocity of a particle normal to the solid wall due its interaction with a collapsing bubble